Empowering Women, Enhancing Essential Oils: Gender-Responsive Patchouli Seedling Enterprises in Aceh, Indonesia - Suraiya Kamaruzzaman; Irfan Zikri; Ernawati Ernawati; Friesca Erwan (Winaya Inspirasi Nusantara Foundation, 2026)
Desa Teuladan in Aceh Besar has significant potential for patchouli (Pogostemon Cablin Benth.) production. However, the development is constrained by limited access to quality local seedlings, weak institutional structures, and low women’s participation. This study aims to promote inclusive entrepreneurship through gender-responsive approaches, focusing on strengthening technical skills, establishing seedling enterprises, and fostering local economic institutions. Using Participatory Action Research (PAR) and gender mainstreaming principles, this study conducted training on seedling cultivation, organic composting, and basic business management, while facilitating the formation of women-led entrepreneurial groups and developing operational tools, including training modules, SOPs, and digital record-keeping systems. The initiative produces 1,500 high-quality seedlings with a 95% survival rate and establishes the Desa Teuladan Inclusive Patchouli Enterprise. The initiative also increases women’s empowerment, improves household income, and encourages more sustainable agricultural practices. These outcomes demonstrate a replicable model of gender-inclusive entrepreneurship that contributes to local development and university-community collaboration.